2022
DOI: 10.1177/15353702221102901
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Nigeria medicinal herbal remedies: A potential source for therapeutic against rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a debilitating disease associated with locomotion impairment, and conventional therapeutic drugs are not optimal for managing RA. There is an avalanche of medications used for the management of RA. Still, studies have shown that they are associated with severe side effects, including hepatotoxicity, retinopathy, and cardiotoxicity disorders of the central nervous system (CNS), skin, blood, and infections. Complementary and alternative medicine (CAM) is currently gaining attention a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 278 publications
1
3
0
Order By: Relevance
“…The secretion of FADD by microvesicles and the extracellular secretion of FADD were shown to be regulated by adenosine and adenosine receptors ( Tourneur et al, 2008 ). Our study revealed a significant reduction in adenosine levels within the FCA model, which aligns with previous observations in the FCA model of female Wister rats ( Arunsi et al, 2022 ). Furthermore, previous research showed that FCA-treated Sprague-Dawley rats exhibit a lower level of cAMP (an adenosine precursor) ( Antwi et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…The secretion of FADD by microvesicles and the extracellular secretion of FADD were shown to be regulated by adenosine and adenosine receptors ( Tourneur et al, 2008 ). Our study revealed a significant reduction in adenosine levels within the FCA model, which aligns with previous observations in the FCA model of female Wister rats ( Arunsi et al, 2022 ). Furthermore, previous research showed that FCA-treated Sprague-Dawley rats exhibit a lower level of cAMP (an adenosine precursor) ( Antwi et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation of the joints accompanied by severe joint pain, swelling, and joint damage, ultimately leading to joint destruction and loss of function (Arunsi, Chioma, Etusim, & Owumi, 2022; Wang et al., 2022). Although the prognosis for patients with RA has improved over the past few decades, most patients still do not achieve adequate disease control (Silvagni et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Downsides associated with available allopathic remedies necessitate the development of multi-oriented, efficacious, and safe therapies for ulcerative colitis. Herbal mode of therapy is gaining much attention worldwide as an alternative approach ( Arunsi et al, 2022 ). Herbs have the potential to cure gastrointestinal issues including ulcerative colitis ( Dubey et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%